Painting & Sculpture - Daniel Chester French (Wikimedia Commons, 1899)
Notice iconographique issue de Wikimedia Commons. Titre: Painting & Sculpture. Sculpture | Sculpture
Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons